The Impact of Concurrent Linguistic Tasks on Participants' Identification of Spearcons. (November 2019) - Davidson, Thomas J.; Ryu, Younji; Brecknell, Birgit; Loeb, Robert G.; Sanderson, Penelope M.
Spearcons (time-compressed speech) may be a viable display for patient monitoring, but the impact of concurrent linguistic tasks on spearcons has not been examined. We tested whether different concurrent linguistic tasks worsen participants' identification of spearcons. Experiment 1 tested participants' identification of spearcons representing 2 vital signs of 5 patients while participants did either no concurrent task, reading, or saying linguistic tasks. Experiment 2 tested identification of 48 single patient-monitoring spearcons while participants did no concurrent task, reading, listening, and saying linguistic tasks. In Experiment 1 the saying task worsened participants' identification of spearcons compared with the other tasks. In Experiment 2, the saying and listening tasks each reduced participants' accuracy at identifying spearcons, but the reading task did not. Listening had no more effect than the saying task did. Concurrent listening and saying tasks worsen participants' identification of spearcons, probably due to auditory modality interference in working memory.